A multi-timescale cold storage system within energy flexible buildings for power balance management of smart grids. (December 2020) - Yan, Chengchu; Wang, Fengling; Pan, Yan; Shan, Kui; Kosonen, Risto
Abstract: Energy storage is widely used in energy flexible buildings, which have great potential for relieving the power imbalance of electrical grids. However, most of the existing energy storage systems are designed for short-term storage, and only a few systems reported for long-term or multi-time scale storage. This paper introduces a new type of multi-timescale cold storage system consisted of a heat pipe-based natural ice storage subsystem and a dual-operation chiller for buildings to enhance their energy flexibility. The proposed system operated in different modes to provide the seasonal cold storage, nighttime chilled water storage, and urgent demand response services, which can be used for relieving the power imbalance in the timescale of the long-term, short-term and real-time respectively. The working principle, system configuration, operation modes, and the implementation of the proposed system for multi-timescale power management, are presented. A case study has been conducted in a building in Beijing to demonstrate the application and effectiveness. Results show that building load factors are greatly improved seasonally (from 19.5% to 49.5%) and daily (from 55.7% to 72.2%), and the power consumption is also considerably decreased (41.2%) during the demand response (DR) event. Highlights: A cross-timescale cold storage system is proposed for energy flexible buildings. Three energy management strategies applied for energy flexibility enhancement. The system can be used to relieve the power imbalance in different timescales. Load factor improved from 19.5% to 49.5% seasonally and from 55.7% to 72.2% daily. The power consumption is considerably decreased (41.2%) during the DR event.